A composição do espetáculo “Uma viagem ao céu”: diálogos entre a música-teatro e a referencialidade - Lima Júnior, José Adriano de Sousa (2022)
The aim of this study is to approach about the characteristics related to the music theater genre (SALZMAN & DÉSI, 2008) associated with the study of intertextual procedures (LIMA 2011, KRISTEVA, 1967; BAKHTIN, 1988; FIORIN, 2006 e KAPLAN 2006). As a result, it will be considered the compositional process of the show "Uma Viagem ao céu", that was composed and structured correlating some aspects from Northwestern Oral Tradition Culture addressed in the cordel literature "Uma viagem ao céu" by Leandro Gomes de Barros (1865-1918), and songs of Cancioneiro da Paraíba (SANTOS; BATISTA, 1993). The music theater is a form of valid artistically understanding that was able to embrace the musical reality which emerged after the Second World War. Besides housing the unprecedented forms of musical and theatrical expression that were discovered in the second half of the 20th century, thus encompassing several possibilities of compositional techniques, be they gestures, semantics, electronic devices, or the like. The master thesis was organized in three chapters. In the first chapter, it was approached specific topics of music theater, its characteristics, as well as, to link some examples removed from show. In chapter two, it was considered the composition from the viewpoint of intertextuality, of cordel literature and what its importance is in the context of the chosen genre. And, the last chapter was addressed to the formative parts of the show “Uma viagem ao céu”, its the respective scenes, commenting on excerpts from the compositional process and the use of the characteristics of the music theater genre, the tools of intertextuality, and their respective compositional strategies.